2015
DOI: 10.1186/s12893-015-0018-0
|View full text |Cite
|
Sign up to set email alerts
|

Outcome after surgery for acute right-sided colonic ischemia without feasible vascular intervention: a single center experience of 58 patients over 6 years

Abstract: BackgroundThe predilection site of non-occlusive mesenteric ischemia is the right-sided colon. Surgical exploration followed by segmental bowel resection and primary anastomosis or ileostomy is recommended, if vascular interventions are not feasible and conservative treatment fails. We assessed the outcome of patients in this life-threatening condition.MethodsFrom a prospective database 58 patients with urgent surgery for acute right-sided colonic ischemia without feasible vascular intervention (as a surrogate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Another investigation identified 58 patients with right sided colonic gangrene and concluded that in this subgroup 54% had some degree of mesenteric atherosclerosis present on radiological examination. 219 In one study focusing on fatal isolated colonic ischaemia identified at autopsy, 53 patients were identified. 220 In this study the left colon was most commonly affected, but the caecum was affected in 25%, and the ascending colon in 26%.…”
Section: The Role Of Imagingmentioning
confidence: 99%
“…Another investigation identified 58 patients with right sided colonic gangrene and concluded that in this subgroup 54% had some degree of mesenteric atherosclerosis present on radiological examination. 219 In one study focusing on fatal isolated colonic ischaemia identified at autopsy, 53 patients were identified. 220 In this study the left colon was most commonly affected, but the caecum was affected in 25%, and the ascending colon in 26%.…”
Section: The Role Of Imagingmentioning
confidence: 99%
“…An interruption of the blood supply to the mesenteric vasculature can cause necrosis of the small intestine, which can subsequently lead to serious illness and death. The shortterm mortality of AMI is high, ranging from 26 to 86% [2][3][4], and early diagnosis and timely treatment essential to improve the prognosis of AMI [5].…”
Section: Introductionmentioning
confidence: 99%
“…An interruption of the blood supply to the mesenteric vasculature can cause necrosis of the small intestine, which can subsequently lead to serious illness and death. The short-term mortality of AMI is high, ranging from 26 to 86% [2][3][4] , and early diagnosis and timely treatment essential to improve the prognosis of AMI [5] .…”
Section: Introductionmentioning
confidence: 99%